A guide to successful collaboration in the aerospace industry - Johnson, Terry (Aircraft Engineering, 2003)
The benefits of collaborative solutions are best illustrated using real-life examples. Bell Helicopters, for instance, needed a more effective way of managing large numbers of proposals for the production of helicopters. Traditionally, this had been a complex and time-consuming task. However, NexPrise was able to provide the company with a secure web-based solution that enabled it to easily manage the multistage process of creating proposals across a diverse supplier base.